THE EFFECT OF THE INQUIRY LEARNING MODEL ON SOCIAL SCIENCE LEARNING OUTCOME AND SAINS LITERACY IN GRADE IV STUDENTS OF ELEMENTARY SCHOOL CLUSTER IV AT BEBANDEM DISTRICT - Aditya Pratama, I Wayan Agus Giri; Suwindia , I Gede; Handriani , Luh Gede (Universitas Veteran Bangun Nusantara, 2025)
The focus of this study is to discover how the inquiry learning approach affects science literacy and learning outcomes. The sample consisted of 55 persons chosen by random sampling techniques, while the research population included of 246 people. This study uses a posttest control group design and is quasi-experimental. An essay-style questionnaire measuring learning, motivation, data, and scientific critical thinking abilities was used to gather the study's data. The MANOVA statistical test was used to assess the data. With a F value of 39.457 and a significance level below 0.05, the results of this study show that: 1) the inquiry learning approach has an impact on the scientific learning outcomes of grade IV students at Elementary School Cluster IV, Bebandem District. 2) With a F value of 31.107 and a significance level below 0.05, the inquiry learning model has an impact on the science literacy of grade IV students at Elementary School Cluster IV, Bebandem District. 3) There is an influence of the inquiry learning model on the science learning outcomes and science literacy of grade IV students of Elementary School Cluster IV, Bebandem District. These results are evidenced by the F value of 32.903 with a significance of less than 0.05. This study provides empirical evidence regarding the effectiveness of the inquiry learning model on science learning outcomes and science literacy at the elementary school level.